2014
DOI: 10.1108/ejm-05-2012-0329
|View full text |Cite
|
Sign up to set email alerts
|

Snowball to avalanche

Abstract: Purpose – This paper aims to investigate the determinants of successful online viral marketing. More companies in recent years have reduced their advertising expenditures on traditional media. Instead, they focus more on word-of-mouth marketing to reach their potential customers. Design/methodology/approach – A 2 (high/low utilitarian message context) × 2 (high/low hedonic message context) × 2 (message source: strong/weak tie strength) ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Existing research on communication effectiveness allocates a great deal of interest to how such factors influence attitudes and persuasion (e.g., Karmarkar & Tormala, 2010; Kirmani & Shiv, ; Petty & Cacioppo, ), product purchase intentions (Gilly, Graham, Wolfinbarger, & Yale, ; Yan, Ogle, & Hyllegard, ), or actual sales (Chevalier & Mayzlin, ; Zhu & Zhang, ). The research on sharing marketing messages is even more scant, with extant studies considering message recommendation intentions (Lee & Youn, ), sharing online information (Chiu et al., ), or forwarding e‐mails (Chiu, Hsieh, Kao, & Lee, ). The current research looking at retweeting falls into this category.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing research on communication effectiveness allocates a great deal of interest to how such factors influence attitudes and persuasion (e.g., Karmarkar & Tormala, 2010; Kirmani & Shiv, ; Petty & Cacioppo, ), product purchase intentions (Gilly, Graham, Wolfinbarger, & Yale, ; Yan, Ogle, & Hyllegard, ), or actual sales (Chevalier & Mayzlin, ; Zhu & Zhang, ). The research on sharing marketing messages is even more scant, with extant studies considering message recommendation intentions (Lee & Youn, ), sharing online information (Chiu et al., ), or forwarding e‐mails (Chiu, Hsieh, Kao, & Lee, ). The current research looking at retweeting falls into this category.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, referring to QR codes, Atkinson (2013) suggested that content should be created carefully to provide meaningful, usable information for consumers and that the tendency of 'market mavens' to share information should be harnessed by providing QR code content that is relevant, interesting and easily passed on to other consumers (Atkinson, 2013, p. 387). Chiu et al (2014) looked at digital content, focusing on word of mouth as a dimension of commitment, and they found that people are more willing to share marketing messages with others when the message (the 'say what' factor) contains higher degrees of utilitarian (e.g. product quality and useful information) or hedonic (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The results also align with work demonstrating that online marketing messages with highly rational content (utilitarian) lead to more significant information sharing when high cognitive involvement occurs. Notably, the effectiveness of informational content is greater than that of remunerative content, which results in active engagement in the form of liking and sharing but not passive behavior (consuming) (Chiu et al, 2014). Dolan et al, (2019) indicate that while rational content appears superior to emotional content within social media to drive active consumer engagement, the type of rational content is essential, and content should comprise product-and brand-related information rather than sales-focused promotion such as remunerative content.…”
Section: Audio and Stimuli Effect Consumer Engagementmentioning
confidence: 99%